A preliminary investigation of condensed tannins from mangrove / Maimunah Sokro …[et al.] - Sokro, Maimunah; Tan, Soo Sun; Hassan, Arba 'at; Othman, Hanita (2006)
The condensed tannins of mangrove Rhizophora mucronata were extracted using water, methanol or acetone at different concentrations with or without acidification. Among solvents tested, 70% acetone, containing 1% HCI, extracted a maximum amount of condensed tannins from mangrove. Condensed tannins extracted were assayed using a 0.5% vanillin solution in methanol containing 4% HCI (v/v). Fresh leaves of Rhizophora mucronata contained the lowest amounts of condensed tannins (10%) compared to all other parts of the plant. The percentage of the condensed tannins extracted depend on the age of the mangrove tree, the type and percentage of the solvent used, as well as the type and the concentration of the acid used, and the condition of keeping the extracted tannins aliquot.